2022
DOI: 10.3389/fendo.2022.827032
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Biosynthesis and Signal Transduction in Ovarian Disease

Abstract: Estrogen mainly binds to estrogen receptors (ERs) to regulate menstrual cycles and reproduction. The expression of ERalpha (ERα), ERbeta (ERβ), and G-protein-coupled estrogen receptor (GPER) mRNA could be detected in ovary, suggesting that they play an important role in estrogen signal transduction in ovary. And many studies have revealed that abnormal expression of estrogen and its receptors is closely related to ovarian disease or malignant tumors. With the continuous development and research of animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 163 publications
0
6
0
Order By: Relevance
“…It may also be indicated that ERα and ERβ regulate processes connected with the female reproductive system in regulating several other physiological and pathophysiological processes in the human body. Disrupted ER signaling leads to the development of different diseases, such as osteoporosis, neurodegeneration, inflammation and metabolic and cardiovascular diseases [ 19 ]; however, the most important indications to modify their activity connected with estrogen-related cancers such as breast [ 19 ], endometrial [ 20 ], cervical [ 21 ] and ovarian cancer [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…It may also be indicated that ERα and ERβ regulate processes connected with the female reproductive system in regulating several other physiological and pathophysiological processes in the human body. Disrupted ER signaling leads to the development of different diseases, such as osteoporosis, neurodegeneration, inflammation and metabolic and cardiovascular diseases [ 19 ]; however, the most important indications to modify their activity connected with estrogen-related cancers such as breast [ 19 ], endometrial [ 20 ], cervical [ 21 ] and ovarian cancer [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to tumor-intrinsic genetic factors, the tumor microenvironment is an emerging hallmark of cancer [75] and thus shapes EAOCs. One major player in the malignant transformation to EAOC is the estrogen concentration in the surrounding milieu, either exogenously provided by estrogen replacement therapy [76,77] or endogenously produced by the ovaries [78]. Hereby, high estrogen levels promote the proliferation of endometriotic cells via binding to the non-classical, G-protein-coupled estrogen receptor 1, followed by the activation of various signaling pathways such as the PI3K/AKT/mTOR [79], as reviewed by Kozieł et Piastowska-Ciesielska [80].…”
Section: Estrogen Concentrationmentioning
confidence: 99%
“…GPER is widely distributed in various tissues of the human body. GPER first attracted considerable attention in reproduction as an estrogen receptor that functioned in the breast [ 17 , 20 ], ovary [ 21 ], endometrium [ 22 , 23 ], testis [ 24 ], and prostate [ 25 , 26 ], as well as the placenta [ 27 , 28 ]. GPER is also found in other systems and organs, including the brain, lung, liver, heart, pancreatic islets, adipose tissue, vasculature, muscle, and skeleton, as well as in immune cells [ 29 , 30 ].…”
Section: Tissue Cellular Localization Ligands and Classical Signaling...mentioning
confidence: 99%